Factors That Affecting The Effective Online Collaborative Learning Environment - Razali, Sharifah Nadiyah; Shahbodin, Faaizah; Hussin, Hanipah; Bakar, Norasiken (2014)
Interest in collaboration is a natural outgrowth of the trend in education toward active learning. Many researchers have found advantages of collaborative learning; it improves academic performance, promotes soft skills development (communication, collaboration, problem solving and critical thinking skills) and increases satisfaction in the learning experience. However, several studies have reported the opposite. Therefore, this paper aims to determine the factors to be considered in creating an effective online collaborative learning environment. In order to achieve the aims, this study was conducted qualitatively in the form of a document review. The results indicate three main factors that affect the effectiveness of Online Collaborative Learning Environments as Learning Environment, Learning Design, and Learning Interaction. An Online Learning Interaction model is also proposed according to the results. This study will continue to determine the elements that can clarify all the factors which have been identified in this study.